HLA Fully-Mismatched Sibling-Derived CD7 CAR-T Therapy Bridging to Haploidentical Hematopoietic Stem Cell Transplantation for Hepatosplenic γδ T-cell Lymphoma - Xueer Xu; Cheng Zu; Mingming Zhang; Pingnan Xiao; Ruimin Hong; Jingjing Feng; Huijun Xu; Jiazhen Cui; Jian Yu; Jimin Shi; Guoqing Wei; Alex H. Chang; et al. (Cell Transplantation, 2023)
While chimeric antigen receptor (CAR)-T-cell therapy has demonstrated remarkable effectiveness in the treatment of B-cell lymphomas and leukemias, research on T-cell malignancies is still limited. Here, we reported a patient with hepatosplenic γδ T-cell lymphoma refractory to multiple lines of chemotherapy, who eventually achieved first complete remission with flow cytometry-confirmed minimal residual disease negativity after human leukocyte antigen (HLA) fully-mismatched sibling-derived CD7 CAR-T therapy. However, given the allogeneic nature, CAR-T cells dropped rapidly after a peak of 83.4% of circulating T-cells. Cytokine release syndrome, cytopenia, and infections occurred but were manageable after treatments. After the consolidative haploidentical hematopoietic stem cell transplantation (HSCT), the patient remained in remission at the end of the follow-up (13 months post-CAR-T infusion). This is the first case of relapsed/refractory hepatosplenic γδ T-cell lymphoma who achieved lasting CR after HLA fully-mismatched sibling-derived CD7 CAR-T therapy bridging to haploidentical HSCT.